A consequence analysis study of natural gas consumption in a developing country: Case of India. (October 2020) - Kumar, Vinod Vijay; Shastri, Yogendra; Hoadley, Andrew
Abstract: Natural gas, as the cleanest burning of the fossil fuels is expected to play a significant role in India's future energy mix. This paper presents a modelling approach to quantify the economic and environmental impacts of natural gas utilisation by various sectors in India while the production of domestically sourced natural gas is in decline. One of the most important sectors is the use of natural gas for cooking where the benefits are also evaluated. The long-term impacts of a reducing domestic gas supply is assessed by using the resource-substitution methodology along with a dynamic resource-depletion indicator that is based on decision-making viewpoints. The results show that the replacement of domestic gas with black coal resulted in an increase under the climate change category by 162%, 202% and 234% for the individualist, hierarchist and egalitarian viewpoints, respectively. The paper highlights the prospects for natural gas in India and shows that the growing demand for gas can be met through imports, but it has associated economic and environmental impacts. Further, the paper presents suitable recommendations including policy-related changes such as carbon pricing and subsidy provision schemes to ensure that the growth of the Indian gas market is sustainable. Graphical abstract: Image 1 Highlights: Estimation of demand for natural gas in India using dynamic modelling. Impact analysis of reducing gas supply using resource substitution methodology. Wider environmental benefits of natural gas penetration in cooking sector. Policy-related recommendations for Indian gas market to ensure sustainable growth.